Method for preparing semi-solid energy storage composite electrolyte for gas turbine black start and electrolyte
Patent Information
- Application Number
- CN202611171827.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-08-04
AI Technical Summary
传统燃机黑启动多依赖柴油发电机组作为备用启动电源,存在启动响应慢、运维成本高、污染排放大、功率冲击耐受能力弱、无法兼顾日常电网调频冗余利用等突出短板;而现有全液态锂电池储能虽响应速度快,但易燃易漏、热失控风险高,在电站密闭工况、宽温波动环境下安全隐患突出;全固态电池虽安全性高,但界面阻抗大、低温性能衰减严重、大倍率冲击放电能力不足,难以适配燃机黑启动瞬时大功率冲击、宽温域运行、长期静置备用的严苛工况需求
1、本发明通过La2Ti2O7@SnO2压电异质结纳米纤维与单宁酸配位自组装的复合改性体系,打破了传统半固态电解质单一填料物理掺杂、无界面调控的性能瓶颈。本发明通过La2Ti2O7@SnO2压电异质结纳米纤维,利用压电极化效应与界面能带弯曲产生内建电场,有效促进锂盐解离、构建长程连续锂离子传输通路;同时采用单宁酸实现原位配位自组装,在电极界面形成均匀致密有机-无机复合钝化层,既可以屏蔽阴离子迁移、降低界面极化,又能规整锂离子沉积行为,从材料本源同步解决离子传导弱、界面不稳定、枝晶易生长三大难题;
Smart Images

Figure CN122696765B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage and black start technology of power systems, specifically relating to the preparation method and electrolyte of semi-solid energy storage composite electrolyte for black start of gas turbines. Background Technology
[0002] With the high proportion of new energy sources integrated into the new power system and the increasingly complex power grid structure, the risk of large-scale power outages caused by extreme weather and line faults continues to rise. Gas turbine black start has become a key core technology for building a robust local power grid and rapidly restoring power grid faults. Traditional gas turbine black start relies mainly on diesel generator sets as backup starting power sources, which has prominent shortcomings such as slow start-up response, high operation and maintenance costs, large pollution emissions, weak power surge tolerance, and inability to take into account the redundancy utilization of daily power grid frequency regulation. While existing all-liquid lithium battery energy storage has a fast response speed, it is flammable and prone to leakage, and has a high risk of thermal runaway, posing significant safety hazards in the closed operating conditions of power plants and wide temperature fluctuation environments. Although all-solid-state batteries have high safety, they have high interface impedance, severe low-temperature performance degradation, and insufficient high-rate surge discharge capability, making them unsuitable for the stringent operating conditions of gas turbine black start, such as instantaneous high-power surges, wide temperature range operation, and long-term static standby.
[0003] Currently, semi-solid-state lithium batteries adapted for gas turbine black start still face numerous technical bottlenecks: Existing semi-solid electrolytes mostly employ single polymer physical blending modification, resulting in low ionic conductivity and significant attenuation of ion transport capacity at low temperatures, failing to meet the instantaneous high-rate discharge requirements of black start; Conventional inorganic fillers are prone to agglomeration, involving only simple physical doping and lacking built-in electric field regulation mechanisms, leading to weak lithium salt dissociation capabilities and easy formation of lithium dendrites during cycling, causing rapid capacity decay and reduced safety performance; Simultaneously, the electrolyte-electrode interface has poor compatibility, easily deteriorating under frequent power surges during black start, with continuously increasing interface impedance, severely shortening the backup cycle life of energy storage batteries. Furthermore, existing electrolyte systems lack sufficient high-voltage withstand capability, making it difficult to adapt to the operational requirements of high-voltage energy storage series-parallel modules in power plants, and lacking dedicated interface coordination regulation mechanisms, failing to simultaneously meet the four core operating conditions of black start: instantaneous high-power surges, wide temperature range adaptability, long-cycle static standby, and high safety without thermal runaway.
[0004] Therefore, developing a dedicated semi-solid composite electrolyte that is suitable for gas turbine black start scenarios and possesses high ionic conductivity, stable ion transport over a wide temperature range, resistance to high-rate power surges, strong dendrite suppression capability, high-voltage interface stability, and long cycle and long static life is an urgent need to solve the safety and performance bottlenecks of existing black start energy storage batteries and support the construction of a robust power grid for new power systems.
[0005] To this end, a method for preparing a semi-solid energy storage composite electrolyte for black start of gas turbines and the electrolyte itself are proposed. Summary of the Invention
[0006] The present invention aims to at least solve one of the technical problems existing in the prior art, and provides a method for preparing a semi-solid energy storage composite electrolyte for black start of gas turbines and the electrolyte itself.
[0007] One aspect of the present invention provides a method for preparing a semi-solid energy storage composite electrolyte for black start of gas turbines, comprising the following steps: S1. Preparation of precursor nanofiber membranes; S2. Based on the aforementioned precursor nanofiber membrane, La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers are prepared using a hydrothermal-annealing method. S3. An electrolyte precursor solution is prepared by means of the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers, composite polymer matrix, composite plasticizer, conductive lithium salt, and coordination self-assembly agent. S4. The electrolyte precursor solution is coated onto the substrate surface, and then subjected to natural gradient evaporation, segmented curing process and vacuum drying to obtain the composite electrolyte.
[0008] Furthermore, the preparation method of the precursor nanofiber membrane includes the following steps: Lanthanum acetate, tetrabutyl titanate or titanium isopropoxide and polyvinylidene fluoride-hexafluoropropylene copolymer are added to a mixed solvent of N,N-dimethylformamide and acetone in a set mass ratio, and a chelating stabilizer is added dropwise. The mixture is then magnetically stirred to obtain an electrospinning precursor solution. The electrospinning precursor liquid was loaded into a syringe, and electrospinning was carried out under preset working voltage, receiving distance, propulsion speed, temperature and humidity conditions to collect nascent nanofiber membranes. The nascent nanofiber membrane was vacuum dried to obtain the precursor nanofiber membrane.
[0009] Specifically, the operating voltage is 17kV to 26kV, the receiving distance is 13cm to 21cm, and the propulsion rate is 0.35mL·h. -1 ~0.75mL·h -1 The ambient temperature is 22℃~29℃ and the ambient humidity is 28%~48%.
[0010] Specifically, the volume ratio of N,N-dimethylformamide to acetone in the mixed solvent is 7:3; the molar ratio of lanthanum to titanium in the electrospinning precursor solution is 1:1.
[0011] Furthermore, the preparation method of the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers is as follows: Prepare an aqueous solution of tin tetrachloride with a concentration of 0.06 mol / L to 0.14 mol / L; The precursor nanofiber membrane was vertically immersed in the tin tetrachloride aqueous solution and placed in a preset constant temperature hydrothermal environment for heat preservation reaction; After the reaction is complete, the precursor nanofiber membrane is taken out and washed sequentially with deionized water and anhydrous ethanol to remove unreacted ions and residual impurities from the surface. The washed nanofiber membrane is placed in a reaction furnace and heated to a preset temperature at a preset heating rate under an air atmosphere. After constant temperature annealing, it is naturally cooled to room temperature to obtain the La2Ti2O7@SnO2 piezoelectric heterojunction nanofiber.
[0012] Furthermore, the preparation method of the electrolyte precursor solution includes the following steps: The composite polymer matrix is added to the composite plasticizer, and the mixture is magnetically stirred under preset water bath conditions to obtain a mixed solution. A predetermined mass fraction of conductive lithium salt and the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers were sequentially added to the mixed solution. After ultrasonic dispersion and magnetic stirring, a coordination self-assembly agent was added, and the electrolyte precursor solution was obtained by stirring.
[0013] Specifically, the composite polymer matrix includes polyvinylidene fluoride-hexafluoropropylene copolymer and polyethylene oxide; the composite plasticizer is obtained by compounding fluoroethylene carbonate and dimethyl carbonate.
[0014] Specifically, the composite polymer matrix comprises 80-95 parts by mass; the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers comprise 4-12 parts by mass, and the fiber diameter of the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers is 200nm-500nm; the coordination self-assembly agent is tannic acid, and comprises 1.0-3.5 parts by mass; the conductive lithium salt is one of LiTFSI and LiFSI, and comprises 6-15 parts by mass; the composite plasticizer is composed of fluoroethylene carbonate and dimethyl carbonate, and the mass parts of fluoroethylene carbonate and dimethyl carbonate are 3-8 parts and 8-18 parts, respectively.
[0015] Furthermore, the segmented ripening process includes the following steps: The temperature was kept at 35℃~42℃ for 3h~5h and then raised to 45℃~55℃ and kept for 2h~4h.
[0016] Another aspect of the present invention provides a semi-solid energy storage composite electrolyte for black start of gas turbines. The composite electrolyte is prepared by the above-described method for preparing a semi-solid energy storage composite electrolyte for black start of gas turbines, and includes a composite polymer matrix, a conductive lithium salt, a composite plasticizer, La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers dispersed in the composite polymer matrix, and a coordination crosslinking structure formed by tannic acid; the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers form a continuous ion transport network in the composite polymer matrix.
[0017] The beneficial effects of this invention are as follows: 1. This invention breaks through the performance bottleneck of traditional semi-solid electrolytes with single filler physical doping and no interface regulation by using a composite modification system of La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers and tannic acid coordination self-assembly. Through La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers, this invention utilizes the piezoelectric polarization effect and interfacial band bending to generate a built-in electric field, effectively promoting lithium salt dissociation and constructing a long-range continuous lithium-ion transport pathway. Simultaneously, tannic acid is used to achieve in-situ coordination self-assembly, forming a uniform and dense organic-inorganic composite passivation layer at the electrode interface. This layer can shield anion migration, reduce interfacial polarization, and regulate lithium-ion deposition behavior, thus simultaneously solving the three major problems of weak ion conduction, interface instability, and easy dendrite growth from the material's fundamental source. 2. This invention employs a natural gradient solvent regulation and segmented ripening process, mechanistically adapting to the core requirements of semi-solid batteries: wide temperature range, long cycle life, and high voltage adaptability. By using a natural gradient solvent regulation process to retain trace amounts of plasticizer to construct a semi-solid flexible gel network, the crystallinity of the composite polymer matrix is effectively reduced, improving chain segment mobility and low-temperature ion conductivity. Simultaneously, one-dimensional La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers form a rigid support network within the composite polymer matrix, enhancing the electrolytic mechanical strength and physically preventing lithium dendrite penetration. The tannic acid interface coordination layer can withstand high-voltage oxidation, inhibiting transition metal dissolution and interfacial side reactions, achieving a synergistic improvement in four aspects: high ion conductivity, strong mechanical toughness, stable interface protection, and wide temperature range adaptability. 3. The raw materials used in this invention are readily available and the preparation process is mild and controllable, possessing strong industrial adaptability and economic advantages. Specifically, the polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, lanthanum acetate, tetrabutyl titanate or titanium isopropoxide, tin tetrachloride, tannic acid, conductive lithium salt, and composite plasticizer used in this invention are all common industrial raw materials, requiring no rare or expensive reagents. Furthermore, the entire process employs conventional techniques such as electrospinning, in-situ growth, solution blending, and segmented ripening, offering a wide process window, adjustable parameters, recyclable and reusable solvents, low preparation costs, and the ability to scale up production. It is suitable for various types of semi-solid-state batteries, including shaped, cylindrical, and flexible pouch cells, and has broad prospects for large-scale application. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the steps in preparing a semi-solid energy storage composite electrolyte for black start of a gas turbine according to a specific embodiment of the present invention. Figure 2 This is a schematic diagram showing the ionic conductivity test results of the semi-solid energy storage composite electrolyte for gas turbine black start prepared in Examples 1 to 12 and Comparative Examples 1 to 3 of the present invention at 25°C. Figure 3 SEM image of the semi-solid energy storage composite electrolyte for black start of gas turbine prepared in Example 8 of the present invention. Detailed Implementation
[0019] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] The method for preparing a semi-solid energy storage composite electrolyte for black start of a gas turbine provided in this invention includes the following steps: S1, preparing a precursor nanofiber membrane; S2, preparing La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers based on the precursor nanofiber membrane using a hydrothermal-annealing method; S3, preparing an electrolyte precursor liquid using the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers, a composite polymer matrix, a composite plasticizer, a conductive lithium salt, and a coordination self-assembly agent; S4, coating the electrolyte precursor liquid onto the surface of a substrate, and sequentially subjecting it to natural gradient evaporation, segmented curing processes, and vacuum drying to obtain the composite electrolyte.
[0021] Further, the preparation method of the precursor nanofiber membrane includes the following steps: lanthanum acetate, tetrabutyl titanate or titanium isopropoxide, and polyvinylidene fluoride-hexafluoropropylene copolymer are added to a mixed solvent of N,N-dimethylformamide and acetone in a set mass ratio, and a chelating stabilizer is added dropwise. The mixture is then magnetically stirred to obtain an electrospinning precursor solution. The electrospinning precursor solution is loaded into a syringe, and electrospinning is performed under a preset working voltage, receiving distance, propulsion rate, temperature, and humidity environment to collect the nascent nanofiber membrane. The nascent nanofiber membrane is then vacuum dried to obtain the precursor nanofiber membrane.
[0022] Specifically, the operating voltage is 17kV to 26kV, the receiving distance is 13cm to 21cm, and the propulsion rate is 0.35mL·h. -1 ~0.75mL·h -1 The ambient temperature is 22℃~29℃ and the ambient humidity is 28%~48%.
[0023] Specifically, the volume ratio of N,N-dimethylformamide to acetone in the mixed solvent is 7:3; the molar ratio of lanthanum to titanium in the electrospinning precursor solution is 1:1.
[0024] Further, the preparation method of the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers is as follows: prepare an aqueous solution of tin tetrachloride with a concentration of 0.06mol / L to 0.14mol / L; vertically immerse the precursor nanofiber membrane in the aqueous solution of tin tetrachloride and place it in a preset constant temperature hydrothermal environment for heat preservation reaction; after the reaction is completed, take out the precursor nanofiber membrane and wash it with deionized water and anhydrous ethanol in sequence to remove unreacted ions and residual impurities on the surface; place the washed nanofiber membrane in a reaction furnace, heat it to a preset temperature at a preset heating rate in an air atmosphere, anneal it at a constant temperature, and naturally cool it to room temperature to obtain the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers.
[0025] Further, the preparation method of the electrolyte precursor solution includes the following steps: adding the composite polymer matrix to the composite plasticizer, and magnetically stirring under a preset water bath condition to obtain a mixed solution; adding a preset mass fraction of conductive lithium salt and the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers sequentially to the mixed solution, and after ultrasonic dispersion and magnetic stirring, adding a coordination self-assembly agent, and stirring to obtain the electrolyte precursor solution.
[0026] Specifically, the composite polymer matrix includes polyvinylidene fluoride-hexafluoropropylene copolymer and polyethylene oxide; the composite plasticizer is obtained by compounding fluoroethylene carbonate and dimethyl carbonate.
[0027] Specifically, the composite polymer matrix comprises 80-95 parts by mass; the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers comprise 4-12 parts by mass, and the fiber diameter of the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers is 200nm-500nm; the coordination self-assembly agent is tannic acid, and comprises 1.0-3.5 parts by mass; the conductive lithium salt is one of LiTFSI and LiFSI, and comprises 6-15 parts by mass; the composite plasticizer is composed of fluoroethylene carbonate and dimethyl carbonate, and the mass parts of fluoroethylene carbonate and dimethyl carbonate are 3-8 parts and 8-18 parts, respectively.
[0028] Specifically, the segmented curing process includes the following steps: sequentially maintaining a constant temperature of 35℃~42℃ for 3h~5h and then raising the temperature to 45℃~55℃ and maintaining it for 2h~4h.
[0029] Based on the above embodiments, lanthanum acetate, tetrabutyl titanate or titanium isopropoxide, and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) were added to a mixed solvent of N,N-dimethylformamide (DMF) and acetone at a mass ratio of 0.2–0.4:0.15–0.3:1, with a volume ratio of 7:3. The molar ratio of lanthanum (La) to titanium (Ti) was controlled at 1:1. Glacial acetic acid or acetylacetone was added dropwise as a chelating stabilizer to prevent the hydrolysis of tetrabutyl titanate or titanium isopropoxide. The mixture was magnetically stirred at room temperature for 2–6 hours until the solute was completely dissolved and the system was homogeneous, transparent, and free of agglomerated particles, thus obtaining the electrospinning precursor solution. The electrospinning precursor solution was loaded into a syringe, and the electrospinning working voltage was set to 17 kV–26 kV, the receiving distance to 13 cm–21 cm, and the propulsion rate to 0.35 mL·h. -1 ~0.75mL·h -1 Electrospinning was carried out at a temperature of 22℃~29℃ and a humidity of 28%~48%; the nascent nanofiber membranes were collected, smoothly peeled off, and placed in a vacuum oven to dry for 6h~10h at 45℃~65℃ and a vacuum of 0.085MPa~0.095MPa to completely remove residual organic solvents, thus obtaining the precursor nanofiber membrane, which was sealed, dried, and stored for later use.
[0030] In this embodiment, a tin tetrachloride aqueous solution with a concentration of 0.06 mol / L to 0.14 mol / L was prepared. The precursor nanofiber membrane prepared in the above embodiment was vertically immersed in the reaction solution and kept at a constant temperature hydrothermal environment of 85℃ to 98℃ for 8h to 12h. After the reaction, the precursor nanofiber membrane was taken out and washed repeatedly with deionized water and anhydrous ethanol 3 to 4 times each, with each wash lasting no less than 6min, to remove unreacted ions and residual impurities on the surface. After washing, the precursor nanofiber membrane was placed in a muffle furnace and heated to 500℃ to 580℃ at a heating rate of 3℃ / min to 5℃ / min in an air atmosphere. Then, it was annealed at a constant temperature for 2h to 4h and naturally cooled to room temperature to obtain La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers with a fiber diameter of 200nm to 500nm.
[0031] In this embodiment, 80-95 parts by weight of a composite polymer matrix are taken, and a composite plasticizer prepared from fluoroethylene carbonate (FEC) and dimethyl carbonate (DMC) is added, wherein the mass parts of FEC and DMC are 3-8 parts and 8-18 parts, respectively. The mixture is magnetically stirred for 2-6 hours under a water bath at 25°C-60°C to allow the polymer to fully swell and dissolve. Subsequently, 6-15 parts by weight of LiFSI or LiTFSI conductive lithium salt and 4-12 parts by weight of La2Ti2O7 are added sequentially. SnO2 piezoelectric heterojunction nanofibers were first ultrasonically dispersed for 30-60 minutes, followed by magnetic stirring for 3-5 hours to ensure uniform dispersion and no agglomeration of La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers in the system. Finally, 1.0-3.5 parts by weight of tannic acid coordination self-assembly agent were added, and the mixture was stirred at room temperature for 4-8 hours. The multidentate hydroxyl groups chelated and coordinated with lithium ions, polymer segments, and the surface of inorganic fillers to form a semi-solid electrolyte precursor solution. This electrolyte precursor solution exhibited uniform cross-linking and strong stability.
[0032] In this embodiment, the prepared electrolyte precursor solution is uniformly coated onto a clean polytetrafluoroethylene (PTFE) plate using a scraper, with the coating thickness controlled at 80 μm to 150 μm. The plate is then allowed to stand at room temperature for 15 to 30 minutes for natural gradient evaporation to regulate the residual solvent content and maintain the semi-solid gel characteristics. Subsequently, it is transferred to an oven and subjected to a segmented curing process: the first segment involves holding the plate at 35°C to 42°C for 3 to 5 hours to achieve a mildly coordinated crosslinked and stable network structure; the second segment involves heating to 45°C to 55°C and holding for 2 to 4 hours to further improve crosslinking and enhance the mechanical toughness of the membrane; after curing, the plate is placed in a vacuum oven and dried at 55°C to 65°C and a vacuum of 0.085 MPa to 0.095 MPa for 6 to 10 hours, ultimately yielding a composite electrolyte with high ionic conductivity, a wide electrochemical window, strong mechanical strength, and interfacial stability.
[0033] Specifically, this invention uses at least one of PVDF-HFP and polyethylene oxide (PEO) as a composite polymer matrix, La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers as functional modified fillers, tannic acid as an interfacial coordination self-assembly agent, and conductive lithium salt and composite plasticizer to construct a semi-solid gel system; one-dimensional La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers are prepared by electrospinning and in-situ growth, and the built-in electric field at the heterojunction interface is used to enhance lithium salt dissociation and lithium ionization. The electrolyte continuously transports molecules; simultaneously, it coordinates and chelates with the lithium anode and polymer segments through the polyphenolic hydroxyl structure of tannic acid, spontaneously constructing a dense and stable artificial passivation interface layer in situ at the electrolyte-electrode interface; a semi-solid composite electrolyte is prepared using a natural gradient solvent regulation and segmented ripening process, forming an integrated structure composed of a La2Ti2O7@SnO2 piezoelectric heterojunction nanofiber conductive network, a tannic acid coordination interface layer, and a composite polymer matrix, which is matched with lithium iron phosphate, ternary high-voltage cathode, and lithium metal anode to assemble a semi-solid lithium battery.
[0034] In another embodiment, the present invention also provides a semi-solid energy storage composite electrolyte for black start of gas turbines. The composite electrolyte is prepared by the above-described method for preparing a semi-solid energy storage composite electrolyte for black start of gas turbines, and includes a composite polymer matrix, a conductive lithium salt, a composite plasticizer, La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers dispersed in the composite polymer matrix, and a coordination crosslinking structure formed by tannic acid; the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers form a continuous ion transport network in the composite polymer matrix.
[0035] To help better understand the present invention, the following embodiments of this application disclose a part of the specific implementation process and comparative process of the preparation method of semi-solid energy storage composite electrolyte for black start of gas turbine. The specific implementation process and comparative process include the exemplary embodiments 1 to 12 and comparative examples 1 to 3.
[0036] Example 1 provides a method for preparing a semi-solid energy storage composite electrolyte for black start of gas turbines, comprising the following steps: S1. The preparation of precursor nanofiber membranes includes the following steps: Lanthanum acetate, tetrabutyl titanate, and PVDF-HFP were added to a mixed solvent of N,N-dimethylformamide and acetone in a volume ratio of 7:3 at a mass ratio of 0.3:0.23:1. The molar ratio of lanthanum (La) to titanium (Ti) was controlled at 1:1. Glacial acetic acid was added dropwise as a chelating stabilizer to prevent the hydrolysis of tetrabutyl titanate. The mixture was magnetically stirred at room temperature for 4 hours until the solutes were completely dissolved and the system was homogeneous, transparent, and free of agglomerated particles, thus obtaining the electrospinning precursor solution. The electrospinning precursor solution was loaded into a syringe, and the electrospinning operating voltage was set to 22 kV, the receiving distance to 17 cm, and the feed rate to 0.5 mL·h. -1 Electrospinning was performed at 25℃ and 38% humidity. The resulting nascent nanofiber membrane was collected, smoothly peeled off, and placed in a vacuum oven. It was dried at 55℃ and 0.09MPa for 8 hours to completely remove residual organic solvents, thus obtaining the precursor nanofiber membrane. The membrane was then sealed, dried, and stored for later use.
[0037] S2. The preparation of La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers includes the following steps: A 0.10 mol / L tin tetrachloride aqueous solution was prepared. The precursor nanofiber membrane prepared in the above-described method was vertically immersed in the reaction solution and kept at a constant temperature hydrothermal environment of 95°C for 10 h. After the reaction, the precursor nanofiber membrane was removed and washed repeatedly with deionized water and anhydrous ethanol four times each, with each wash lasting no less than 6 min, to remove unreacted ions and residual impurities on the surface. After washing, the precursor nanofiber membrane was placed in a muffle furnace and heated to 550°C at a heating rate of 4°C / min in air atmosphere. It was then annealed at a constant temperature for 3 h and naturally cooled to room temperature to obtain La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers with a fiber diameter of 200 nm to 500 nm.
[0038] S3. The preparation of the electrolyte precursor solution includes the following steps: A composite polymer matrix of 85 parts by mass, comprising 52 parts by mass of PVDF-HFP and 33 parts by mass of PEO, was added. A composite plasticizer prepared from fluoroethylene carbonate (FEC) and dimethyl carbonate (DMC), comprising 5 parts by mass of FEC and 12 parts by mass of DMC, was added. The mixture was magnetically stirred for 4 hours in a water bath at 42.5℃ to allow the polymer to fully swell and dissolve. Subsequently, 10 parts by mass of LiFSI conductive lithium salt and 8 parts by mass of La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers were added sequentially. The mixture was first ultrasonically dispersed for 45 minutes, and then magnetically stirred for another 4 hours to ensure that the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers were uniformly dispersed in the system without agglomeration. Finally, 2.2 parts by mass of tannic acid coordination self-assembly agent were added, and the mixture was stirred at room temperature for 6 hours. The semi-solid electrolyte precursor solution was formed by chelating and coordinating the multidentate hydroxyl groups with lithium ions, polymer segments, and the surface of inorganic fillers.
[0039] S4. The preparation of the composite electrolyte includes the following steps: The prepared electrolyte precursor solution was uniformly coated onto a clean polytetrafluoroethylene (PTFE) plate using a scraper, with the coating thickness controlled at 115 μm. The plate was then allowed to stand at room temperature for 22.5 min for natural gradient evaporation to regulate the residual solvent content and maintain the semi-solid gel characteristics. Subsequently, it was transferred to an oven and subjected to a segmented curing process: the first stage involved maintaining a constant temperature of 38℃ for 4 h to achieve a mildly coordinated crosslinked and stable network structure; the second stage involved raising the temperature to 48℃ and maintaining it for 3 h to further improve crosslinking and enhance the mechanical toughness of the membrane; after curing, the plate was placed in a vacuum oven and dried for 8 h at 60℃ and a vacuum of 0.09 MPa to finally obtain the composite electrolyte.
[0040] Example 2 differs from Example 1 only in that the mass fractions of PVDF-HFP and PEO in step S3 are adjusted to 48 and 37 parts respectively, while the remaining steps and parameters are the same as in Example 1.
[0041] Example 3 differs from Example 1 only in that the mass fractions of PVDF-HFP and PEO in step S3 are adjusted to 60 parts and 27 parts respectively, while the remaining steps and parameters are the same as in Example 1.
[0042] Example 4 differs from Example 1 only in that the mass fraction of La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers in step S3 is adjusted to 5 parts, while the remaining steps and parameters are the same as in Example 1.
[0043] Example 5 differs from Example 1 only in that the mass fraction of La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers in step S3 is adjusted to 11 parts, while the remaining steps and parameters are the same as in Example 1.
[0044] Example 6 differs from Example 1 only in that the mass fraction of tannic acid in step S3 is adjusted to 1.2 parts, while the remaining steps and parameters are the same as in Example 1.
[0045] Example 7 differs from Example 1 only in that the mass fraction of tannic acid in step S3 is adjusted to 3.2 parts, while the remaining steps and parameters are the same as in Example 1.
[0046] Example 8: The only difference between this example and Example 1 is that the voltage of electrospinning in step S1 is adjusted to 20kV, while the other steps and parameters are the same as in Example 1.
[0047] Example 9: The only difference between this example and Example 1 is that the voltage of electrospinning in step S1 is adjusted to 24kV, while the other steps and parameters are the same as in Example 1.
[0048] Example 10: The only difference between this example and Example 1 is that the mass fraction of LiFSI conductive lithium salt in step S3 is adjusted to 7 parts, while the other steps and parameters are the same as in Example 1.
[0049] Example 11: The only difference between this example and Example 1 is that the mass fraction of LiFSI conductive lithium salt in step S3 is adjusted to 13 parts, while the other steps and parameters are the same as in Example 1.
[0050] Example 12 differs from Example 1 only in that the muffle furnace annealing temperature in step S2 is adjusted to 520°C, while the other steps and parameters are the same as in Example 1.
[0051] Comparative Example 1 differs from Example 1 only in that La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers are not added when preparing the composite electrolyte; all other steps and parameters are the same as in Example 1.
[0052] Comparative Example 2 differs from Example 1 only in that tannic acid is not added as a coordination self-assembly agent when preparing the composite electrolyte; all other steps and parameters are the same as in Example 1.
[0053] Comparative Example 3 differs from Example 1 only in that an equal amount of ordinary SnO2 nanoparticles are used to replace La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers when preparing the composite electrolyte. All other steps and parameters are the same as in Example 1.
[0054] The electrolytes prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were subjected to performance testing and the results were analyzed. The test results are shown in the table below. Figure 2 and Figure 3As shown.
[0055]
[0056] Comparative Examples 1 to 3 represent the technical routes of three generations of semi-solid electrolytes: pure dual polymer physical blending, single piezoelectric heterojunction physical doping, and ordinary inorganic particles plus tannic acid coordination. Their performance improves in that order, but each has obvious shortcomings: the pure physical blending system has the worst overall performance due to the high crystallinity of the polymer, discontinuous ion channels, and poor lithium salt dissociation; although single piezoelectric heterojunction doping provides some ion transport channels, it has poor dispersibility and no stable protective layer at the interface; although the ordinary inorganic particles plus tannic acid system improves dispersibility and interface stability, it lacks a built-in electric field and has limited lithium salt dissociation ability.
[0057] Examples 1 to 12 achieved the synergistic effect of the present invention by systematically adjusting parameters such as the ratio of PVDF-HFP to PEO in the composite polymer matrix, the amount of La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers added, the amount of tannic acid, the electrospinning voltage, the concentration of conductive lithium salt, and the annealing temperature: the built-in electric field of the La2Ti2O7@SnO2 piezoelectric heterojunction directionally drives lithium ion migration and effectively promotes lithium salt dissociation; the multi-toothed chelating effect of tannic acid simultaneously realizes fiber dispersion, polymer crosslinking, and in-situ lithium anode formation. SE passivation; natural gradient solvent regulation and low-temperature curing effectively reduce matrix crystallinity. These three factors synergistically improve the electrochemical window, lithium-ion transference number, room-temperature ionic conductivity, and cycle stability of the composite electrolyte. Optimal ranges for each parameter were also identified: by mass fraction, 52 parts PVDF-HFP, 31 parts PEO, 8–11 parts La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers, 2.2 parts tannic acid, a spinning voltage of 20 kV–22 kV, and an annealing temperature of 550 °C for the nanofiber membrane. The composite electrolyte prepared according to these optimal ranges achieves a room-temperature ionic conductivity of 2.61 × 10⁻⁶. -4 With an S / cm, an electrochemical stability window widened to 5.1V, and a lithium-ion transference number of 0.68, lithium symmetric batteries prepared using this composite electrolyte can achieve a capacity retention rate of 91.8% after 1,000 cycles at 0.5C. It has multiple advantages, including high ion conductivity, wide temperature range adaptability, high-voltage oxidation resistance, long-term dendrite suppression, and low interfacial impedance, providing a new industrializable technology path for high-safety, long-life, and wide-temperature-range semi-solid-state lithium batteries.
[0058] In summary, the embodiments disclosed herein have at least the following technical effects: 1. This invention breaks through the performance bottleneck of traditional semi-solid electrolytes with single filler physical doping and no interface regulation by using a composite modification system of La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers and tannic acid coordination self-assembly. Through La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers, this invention utilizes the piezoelectric polarization effect and interfacial band bending to generate a built-in electric field, effectively promoting lithium salt dissociation and constructing a long-range continuous lithium-ion transport pathway. Simultaneously, tannic acid is used to achieve in-situ coordination self-assembly, forming a uniform and dense organic-inorganic composite passivation layer at the electrode interface. This layer can shield anion migration, reduce interfacial polarization, and regulate lithium-ion deposition behavior, thus simultaneously solving the three major problems of weak ion conduction, interface instability, and easy dendrite growth from the material's fundamental source. 2. This invention employs a natural gradient solvent regulation and segmented ripening process, mechanistically adapting to the core requirements of semi-solid batteries: wide temperature range, long cycle life, and high voltage adaptability. By using a natural gradient solvent regulation process to retain trace amounts of plasticizer to construct a semi-solid flexible gel network, the crystallinity of the composite polymer matrix is effectively reduced, improving chain segment mobility and low-temperature ion conductivity. Simultaneously, one-dimensional La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers form a rigid support network within the composite polymer matrix, enhancing the electrolytic mechanical strength and physically preventing lithium dendrite penetration. The tannic acid interface coordination layer can withstand high-voltage oxidation, inhibiting transition metal dissolution and interfacial side reactions, achieving a synergistic improvement in four aspects: high ion conductivity, strong mechanical toughness, stable interface protection, and wide temperature range adaptability. 3. The raw materials used in this invention are readily available and the preparation process is mild and controllable, possessing strong industrial adaptability and economic advantages. Specifically, the PVDF-HFP, PEO, lanthanum acetate, tetrabutyl titanate or titanium isopropoxide, tin tetrachloride, tannic acid, conductive lithium salt, and composite plasticizer used in this invention are all common industrial raw materials, requiring no rare or expensive reagents. Furthermore, the entire process employs conventional techniques such as electrospinning, in-situ growth, solution blending, and segmented ripening, offering a wide process window, adjustable parameters, recyclable and reusable solvents, low preparation costs, and the ability to scale up production. It is suitable for various types of semi-solid-state batteries, including shaped, cylindrical, and flexible pouch cells, and has broad prospects for large-scale application.
[0059] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a semi-solid energy storage composite electrolyte for black start of gas turbines, characterized in that, Includes the following steps: S1. Preparation of precursor nanofiber membranes; S2. Based on the aforementioned precursor nanofiber membrane, La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers are prepared using a hydrothermal-annealing method. S3. An electrolyte precursor solution is prepared by means of the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers, composite polymer matrix, composite plasticizer, conductive lithium salt, and coordination self-assembly agent. S4. The electrolyte precursor solution is coated on the substrate surface and then subjected to natural gradient evaporation, segmented curing process and vacuum drying to obtain the composite electrolyte. The preparation method of the precursor nanofiber membrane includes the following steps: Lanthanum acetate, tetrabutyl titanate or titanium isopropoxide and polyvinylidene fluoride-hexafluoropropylene copolymer are added to a mixed solvent of N,N-dimethylformamide and acetone in a set mass ratio, and a chelating stabilizer is added dropwise. The mixture is then magnetically stirred to obtain an electrospinning precursor solution. The electrospinning precursor liquid was loaded into a syringe, and electrospinning was carried out under preset working voltage, receiving distance, propulsion speed, temperature and humidity conditions to collect nascent nanofiber membranes. The nascent nanofiber membrane was vacuum dried to obtain the precursor nanofiber membrane. The preparation method of the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers is as follows: Prepare an aqueous solution of tin tetrachloride with a concentration of 0.06 mol / L to 0.14 mol / L; The precursor nanofiber membrane was vertically immersed in the tin tetrachloride aqueous solution and placed in a preset constant temperature hydrothermal environment for heat preservation reaction; After the reaction is complete, the precursor nanofiber membrane is taken out and washed sequentially with deionized water and anhydrous ethanol to remove unreacted ions and residual impurities from the surface. The washed nanofiber membrane was placed in a reaction furnace and heated to a preset temperature at a preset heating rate in an air atmosphere. After constant temperature annealing, it was naturally cooled to room temperature to obtain the La2Ti2O7@SnO2 piezoelectric heterojunction nanofiber. The coordination self-assembling agent is tannic acid.
2. The method for preparing the semi-solid energy storage composite electrolyte for black start of gas turbines according to claim 1, characterized in that, The operating voltage is 17kV~26kV, the receiving distance is 13cm~21cm, and the propulsion rate is 0.35mL·h. -1 ~0.75mL·h -1 The ambient temperature is 22℃~29℃ and the ambient humidity is 28%~48%.
3. The method for preparing the semi-solid energy storage composite electrolyte for black start of gas turbines according to claim 1, characterized in that, The volume ratio of N,N-dimethylformamide to acetone in the mixed solvent is 7:3; the molar ratio of lanthanum to titanium in the electrospinning precursor solution is 1:
1.
4. The method for preparing the semi-solid energy storage composite electrolyte for black start of gas turbines according to claim 1, characterized in that, The preparation method of the electrolyte precursor solution includes the following steps: The composite polymer matrix is added to the composite plasticizer, and the mixture is magnetically stirred under preset water bath conditions to obtain a mixed solution. A predetermined mass fraction of conductive lithium salt and the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers were sequentially added to the mixed solution. After ultrasonic dispersion and magnetic stirring, a coordination self-assembly agent was added, and the electrolyte precursor solution was obtained by stirring.
5. The method for preparing the semi-solid energy storage composite electrolyte for black start of gas turbines according to claim 4, characterized in that, The composite polymer matrix includes polyvinylidene fluoride-hexafluoropropylene copolymer and polyethylene oxide; the composite plasticizer is based on a compound of fluoroethylene carbonate and dimethyl carbonate.
6. The method for preparing the semi-solid energy storage composite electrolyte for black start of gas turbines according to any one of claims 1 to 5, characterized in that, The composite polymer matrix comprises 80-95 parts by mass; the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers comprise 4-12 parts by mass, and the fiber diameter of the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers is 200nm-500nm; the tannic acid comprises 1.0-3.5 parts by mass; the conductive lithium salt is one of LiTFSI and LiFSI, and comprises 6-15 parts by mass; the composite plasticizer is composed of fluoroethylene carbonate and dimethyl carbonate, and the fluoroethylene carbonate and dimethyl carbonate comprise 3-8 parts by mass and 8-18 parts by mass, respectively.
7. The method for preparing the semi-solid energy storage composite electrolyte for black start of gas turbines according to claim 1, characterized in that, The segmented ripening process includes the following steps: The temperature was kept at 35℃~42℃ for 3h~5h and then raised to 45℃~55℃ and kept for 2h~4h.
8. A semi-solid energy storage composite electrolyte for black start of gas turbines, characterized in that, The semi-solid energy storage composite electrolyte for black start of gas turbines as described in claim 1 is prepared by a method comprising a composite polymer matrix, a conductive lithium salt, a composite plasticizer, La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers dispersed in the composite polymer matrix, and a coordination crosslinking structure formed by tannic acid; the La2Ti2O7@SnO2 piezoelectric heterojunction nanofibers form a continuous ion transport network in the composite polymer matrix.
Citation Information
Patent Citations
Composite solid electrolyte membrane, preparation method thereof and solid lithium metal battery
CN119725714A
Multilayer composite solid electrolyte as well as preparation method and application thereof
CN120637569A